The impact of acute and chronic resistance training on appetite and energy intake: A scoping review examining resistance exercise and comparisons with other exercise modalities - Panissa, Valéria L.G. [UNESP]; Cardoso, Larissa K.; Rossi, Priscila A.Q. [UNESP]; Fukuda, David H.; Rossi, Fabrício E. [UNESP] (Elsevier, 2024)
Purpose: The effects of exercise on appetite have recently been systematically evaluated with a focus on endurance training (ET). However, resistance training (RT) may induce different adaptations than ET. This scoping review aimed to examine the acute and chronic effects of isolated RT and comparisons with other exercise modalities on appetite-related variables and energy intake. Results: 17 acute studies were identified, six examining isolated RT, while 11 focused on RT intensity, amount of exercise, targeted muscle groups, or comparison with ET and combined training (RT plus ET; CT). Nine chronic studies were identified. Three investigated isolated RT vs control and six manipulated the amount of RT exercise, types of RT, or comparison with ET and CT. Conclusions: Acute RT compared to control conditions appears to induce responses favoring appetite inhibition. While the amount of RT exercise may acutely play a role in the suppression of appetite, while ET seems to have more potential to suppress appetite. Chronic RT does not seem to stimulate compensatory mechanisms; however, there is not clear evidence regarding the role of RT intensity or other exercise modalities. Chronic ET and CT may be more prone to favor appetite inhibition than RT. More comprehensive evaluations including the exploration of multiple appetite-related factors are needed for future studies.
Keywords: Desire to eat; Fullness; Gastrointestinal hormone; Hunger; Strength training